Relationship-building in recovery-oriented mental health practice: valuing the role of emotions - Khoury, Emmanuelle (Intervention)

(untitled) (Ordre des travailleurs sociaux et des thérapeutes conjugaux et familiaux du Québec (OTSTCFQ), 2021)
Despite increased interest in relationships and emotions in social work, not enough is known about the role of emotions in recovery-oriented mental health care settings. Reflecting on my graduate research, I explore the inconsistent understandings and comfort levels with emotions in mental health social work practice. I make connections with findings which show that uneven attempts at relationship-building lead to missed opportunities for connection, understanding, and supporting recovery. I discuss the tensions faced by mental health practitioners implementing recovery-oriented interventions within a new public management and risk reduction paradigm of care and the ways that attending to emotions might help critique or dismantle the status quo. These reflections suggest pathways to resist these tensions through realizing the potential of emotions as a source of knowledge in constructing recovery-oriented mental health care interventions.